Low molecular weight polyethylenimine as a transgenic vector for tumor gene therapy. (February 2015) - Lou, Z; Xing, H; Pan, H; Lou, F; Wang, K; Fang, Y; Han, W; Li, D
Abstract We constructed a polymer composed of a series of small molecule polyethylenimine (PEI) using 4-arm polyethylenimine (PEG) as a core for tumor gene therapy. N, N'-carbonyldiimidazole and N-succinimidyl-3-(2-pyridyldithio) propionate were used as chemical connecting reagents to synthesize 4-arm PEG-PEI2000 and 4-arm PEG-PEI2000-MC11. Chemical characterization was performed using 1H-NMR. The retardation effect of polymers on plasmid DNA was observed using electrophoretic mobility shift and MTT assays to test the toxicity of the polymers. The gene delivery capability of 4-arm PEG-PEI2000 and 4-arm PEG-PEI2000-MC11, and the effect of MC11 were determined by an in vitro gene delivery experiment with human hepatoma HepG2 cells. At a N:P ratio of 3, the 4-arm PEG-PEI2000 could retard successfully plasmid DNA with low toxicity. In experiments in vitro, when the N:P ratio was 30, the gene delivery efficiency of 4-arm PEG-PEI2000 in HepG2 cells was five times that of PEI2000; After connecting ligand MC11, however, the gene delivery efficiency was twice as great. Free MC11 effectively inhibited the gene delivery efficiency of the 4-arm PEG-PEI2000-MC11. Four-arm PEG-PEI2000 has low toxicity and high gene delivery efficiency, and is an effective gene delivery vector after linking ligand MC11.